2011
DOI: 10.1016/j.ajpath.2011.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Contribution of CD44 as a Ligand for E-Selectin during Inflammatory T-Cell Recruitment

Abstract: Endothelial selectins guide the migration of inflammatory T cells to extralymphoid tissues. Whereas Pselectin glycoprotein ligand-1 (PSGL-1) functions as the exclusive ligand for P-selectin, it acts in coordination with additional glycoproteins to mediate Eselectin binding. CD44 can act as one such ligand in neutrophils, but its contribution in inflammatory T lymphocytes remains unexplored. We have used realtime in vivo imaging of the cremasteric and dermal microcirculations to explore the dynamics of leukocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 55 publications
1
49
1
Order By: Relevance
“…However, studies have identified differences in homing molecule expression on CD4 + T cells activated in vivo versus ex vivo, indicating that assessment of endogenous T cells may provide a more accurate analysis of the molecular basis of recruitment of activated T cells (25). To this end, more recently, rapid frame-rate multichannel imaging has allowed analysis of endogenous CD4 + T cell rolling in the inflamed skin, revealing the contributions of endothelial selectins and their ligands to CD4 + T cell rolling at the peak of the CS response (29,30). However, these studies did not extend to analysis of Tregs or CD8 + T cells or examine T cell interactions throughout the entire CS response.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, studies have identified differences in homing molecule expression on CD4 + T cells activated in vivo versus ex vivo, indicating that assessment of endogenous T cells may provide a more accurate analysis of the molecular basis of recruitment of activated T cells (25). To this end, more recently, rapid frame-rate multichannel imaging has allowed analysis of endogenous CD4 + T cell rolling in the inflamed skin, revealing the contributions of endothelial selectins and their ligands to CD4 + T cell rolling at the peak of the CS response (29,30). However, these studies did not extend to analysis of Tregs or CD8 + T cells or examine T cell interactions throughout the entire CS response.…”
Section: Discussionmentioning
confidence: 99%
“…Although we identified PSGL-1 as the dominant functional P-selectin ligand on Tregs, consistent with observations in other leukocyte subsets (55,56), identifying the functional E-selectin ligands on Tregs is likely to be more challenging. Several leukocyte-expressed E-selectin ligands, including PSGL-1, E-selectin ligand-1, CD44, and CD43, have been identified (9,30,(56)(57)(58). Expression of E-selectin ligand-1 has not been reported on lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations